Student Perceptions of a Synchronous Online Cooperative Learning Course in a Japanese Women's University during the COVID-19 Pandemic - Chie Sugino (MDPI AG, 2021)
As the coronavirus disease 2019 (COVID-19) pandemic expanded worldwide, most Japanese universities launched online learning as an emergent measure; hence, securing the quality of online learning remains a challenge. This study aimed to understand reasons behind students' preferred mode of online learning during the pandemic and to explore the impact of online cooperative learning on students' class participation by analyzing their voluntary comments. A qualitative content analysis identified three factors that are related to students' decisions and motivation about participating in synchronous online classes: mutuality resulting from interaction, the impact of COVID-19 on their life and learning, and individual circumstances. This small-scale study was conducted under the unusual circumstance of the pandemic, and the quality of student interaction was excluded from the analysis. However, their enjoyment arising from interaction encouraged their participation in a synchronous class and discussion. They expressed themselves and listened to others attentively, creating a favorable climate for learning. Students' positive interdependence observed in this study suggests that cooperative learning cultivates a classroom culture where students are willing to contribute without the fear of losing face. This study indicated that participation, cooperation, and active engagement create a positive feedback loop, promoting each aspect even in an online setting.